Prenatal Stress Inhibits Hippocampal Neurogenesis but Spares Olfactory Bulb Neurogenesis - Belnoue, Laure (Public Library of Science, 2013)
The dentate gyrus (DG) and the olfactory bulb (OB) are two regions of the adult brain in which new neurons are integrated daily in the existing networks. It is clearly established that these newborn neurons are implicated in specific functions sustained by these regions and that different factors can influence neurogenesis in both structures. Among these, life events, particularly occurring during early life, were shown to profoundly affect adult hippocampal neurogenesis and its associated functions like spatial learning, but data regarding their impact on adult bulbar neurogenesis are lacking. We hypothesized that prenatal stress could interfere with the development of the olfactory system, which takes place during the prenatal period, leading to alterations in adult bulbar neurogenesis and in olfactory capacities. To test this hypothesis we exposed pregnant C57Bl/6J mice to gestational restraint stress and evaluated behavioral and anatomic consequences in adult male offspring. We report that prenatal stress has no impact on adult bulbar neurogenesis, and does not alter olfactory functions in adult male mice. However, it decreases cell proliferation and neurogenesis in the DG of the hippocampus, thus confirming previous reports on rats. Altogether our data support a selective and cross-species long-term impact of prenatal stress on neurogenesis.